CBSE Class 8CBSE
Share
Notifications

View all notifications

Solve the Linear Equation M - (M -1)By2 = 1 - (M - 2)By3 - CBSE Class 8 - Mathematics

Login
Create free account


      Forgot password?

Question

Solve the linear equation `m - (m -1)/2 = 1 - (m - 2)/3`

Solution

`m - (m -1)/2 = 1 - (m - 2)/3`

L.C.M. of the denominators, 2 and 3, is 6.

Multiplying both sides by 6, we obtain

6m − 3(m − 1) = 6 − 2(m − 2)

⇒ 6m − 3m + 3 = 6 − 2m + 4 (Openingthe brackets)

⇒ 6m − 3m + 2m = 6 + 4 − 3

⇒ 5m = 7

⇒ `m = 7/5`

  Is there an error in this question or solution?

APPEARS IN

 NCERT Solution for Mathematics Textbook for Class 8 (2018 to Current)
Chapter 2: Linear Equations in One Variable
Ex. 2.50 | Q: 6 | Page no. 34
Solution Solve the Linear Equation M - (M -1)By2 = 1 - (M - 2)By3 Concept: Reducing Equations to Simpler Form.
S
View in app×